Genomic instability in blood cells from bovine with spontaneous tumours: an OneHealth perspective - Freire, E.; Maia, G.; Saraiva, C.; Esteves, A.; Fontes, M. C.; Cardoso, L.; Pires, I.; Gaivão, I. (Spanish Journal of Environmental Mutagenesis and Genomics, 2023)
Genomic instability is a hallmark of carcinogenesis, that acts in the conversion of a normal into a premalignant cell. The aim of this preliminary study, is evaluate DNA damage in different spontaneous tumours, as well as establish a correlation between malignity and the DNA damage itself. OneHealth is a recent approach that links animal with human medicine which is nowadays more relevant. In order to perform this study, the alkaline comet assay was performed on blood samples from 5 animals with neoplastic disease: 2 cutaneous melanomas, 1 cutaneous papilloma, 1 vesical hemangiosarcoma and 1 undifferentiated tumour. The results obtained from DNA damage in blood lymphocytes (in arbitrary units 0-400) were 20±5.34 in the cutaneous papilloma; 22±8.50 and 34±10.12 in the two cutaneous melanomas; 89±19.12 in the vesical hemangiosarcoma and 168±5.5 in the undifferentiated tumour. All animals presented values below 170 A.U., compared to the other cases, the undifferentiated tumour and vesical hemagiosarcoma (which have the higher values) reflect a greater DNA damage. Interestingly, these tumours present histological features suggestive of high biological aggressiveness and distant metastasis. The papilloma, a benign tumour, presented the lowest value. So far results indicate that the damage is higher in aggressive tumours compared to non-invasive tumours. This data belongs to a far more extensive study that will be carried out with the establishment of a control group, as well as obtaining more samples and applying inquests; in order to connect the animals, owners and environmental aspects in an one health perspective of understanding cancer progression. Funding: This work was funded by R&D&I project “oneHcancer – One health approach in animal cancer”, operation no.: NORTE-01-0145-FEDER-000078, co-funded by the European Regional Development Fund (ERDF) through NORTE 2020 (North Portugal Regional Operational Program 2014/2020). Acknowledgments: We would like to thank the CECAV Project-UIDP/00772/2020 funded by the Portuguese Foundation for Science and Technology (FCT).